REPRESENTASI MATEMATIS SEBAGAI ALAT UNTUK PEMAHAMAN MATEMATIKA YANG LEBIH MENDALAM BAGI SISWA SEKOLAH DASAR - I Komang Sesara Ariyana (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2021)
Representation is a mental picture of the learning process that can be understood through mental development that is in a person and is reflected as visualized in the form of verbal, pictures, or concrete objects. Mathematical representations are expressions of mathematical ideas or concepts presented by students as a model or substitute form of a problem situation that is used to find solutions to the problems they are facing as a result of their interpretation of thoughts. Representation is one of the standard processes in NCTM (2000) which requires every child to be able to represent what is on his mind to be expressed in various forms of representation such as mathematical symbols, oral language, use of physical objects, as well as pictures and tables. The depth of mathematical understanding depends on the child's ability to represent the ideas he/she thinks about. Mathematics learning at the elementary school level is more on the use of physical and concrete objects according to the level of cognitive development. Physical and concrete objects must be the basis for the development of a child's mathematical representation ability so that it makes sense to him/her about mathematics, and even in understanding real-world situations. The purpose of this paper is to describe 1) the notion of mathematical representations, 2) the relationship between mathematical representations and mathematical understanding, 3) the role of mathematical representations, and 4) several examples of mathematical representations in mathematics learning in elementary schools.